Synthesis, Characterization of Novel PLGA Encapsulated Indole Nanoparticles and Study of its cytotoxic potential against A549 lung cancer cell line - Sudip Majumder , , Neha Sharma, Subhra Das, Namita Pandey, Tapasya Srivastava, Debasree Ghosha , (Journal of Applied Pharmaceutical Science, 2018)
Objectives: Indole and its derivatives are gaining importance because of their anti-cancer activity. Here, we have reported the synthesis and characterization of novel polymeric poly D, L-lactide-co-glycolide (PLGA) indole nanoparticles, and investigated their cytotoxic potential against A549 lung cancer cells. Materials and methods: Nanoparticles were synthesized by solvent emulsion-diffusion-evaporation method. Size determination was done by Transmission Electron Microscopy (TEM), encapsulation efficiency using UV-Vis spectra, release kinetics using dialysis, measurement of drug-polymer interaction by Fourier Transform Infra Red Spectroscopy (FTIR) and surface charge by zeta potential. Cell viability of lung cancer cells (A549) was determined by (3-(4,5-dimethylthiazol-2-yl)- 2,5-diphenyltetrazolium bromide (MTT) assay and morphological analysis. Results: Nanoparticles were spherical in shape with an average diameter of 65 nm, encapsulation efficiency was found to be about 78% and zeta potential was −15.2mV. Drug-loaded nanoparticles showed sustained release kinetics fitting well in exponential Higuchi and Zero order Model. FTIR studies showed a broadening of the peak of PLGA indole nanoparticles at 2100-3400 cm-1 indicating the formation of drug-loaded nanoparticles. These nanoparticles showed about 95% cytotoxicity against A549 lung cancer cell lines. Results were supported by visible morphological changes in cells. Conclusion: PLGA encapsulated Indole nanoparticles were stable, having sustained release and good cytotoxic potential.
Keywords: Nanoparticles, biomaterials, polymers,sustained release,cytotoxicity.